SEMINAR TENTANG PELEMBAB KULIT WAJAH DARI EKSTRAK DAUN NANGKA (ATROCARPUS HETEROPHYLLUS LAM.) - Tri Nova Lovena; Aminah S; Nur Ulina M Br Turnip (JURNAL PENGMAS KESTRA (JPK), 2021)
One of the Indonesia plant has the potential to produce a natural antioxidannt is nangka leaf containing flavonoids,saponins, tannins.objectives: tomake preparations creamy nangka leaf extract mask. Method the study was conducted experimentally,the sampelwas extracted by maceration for 3x24 hours using 96% ethanol. The results of the viscous extract is obtained as the active substances with concentrations 5% and 10%. Test preparations test organoleptis, include an examination of its homogeneity, ph preparations and skin moisture. Homogeneity test showed that the mask cream preparations produced were homogeneous, pH range 6-7 and the humidity test with a concentration of 5% obtained an average value and could moisturize the skin and a concentration of 10% obtained an average value of 59.46% could moisturize the skin. Jackfruit leaf extract can be formulated in cream mask preparations and cream jackfruit leaf mask extract preparations can moisturize the skin.